Targeted Drug Delivery Systems for Kidney Diseases - Huang, Xiaohan; Ma, Yanhong; Li, Yangyang; Han, Fei; Lin, Weiqiang (Frontiers in Bioengineering and Biotechnology, 2021)
Kidney diseases have gradually become a global health burden. Along with the development of nanotechnology, many hybrids or nanomaterials have been utilized to promote treatment efficiency with negligible side effects. These therapeutic agents have been successfully applied in many fields. In particular, some efforts have also been made to ameliorate the treatment of kidney diseases through targeted delivery nanomaterials. Though most of the delivery systems have not yet been transmitted into clinical use or even still at an early stage, they have shown great potential in carrying immunosuppressants like tacrolimus and triptolide, antioxidants, or siRNAs. Excitingly, some of them have achieved significant treatment effectiveness and reduced systemic side effect in kidney disease animal models. Here, we have reviewed the recent advances and presented nanotherapeutic devices designed for kidney targeted delivery.